Kinetic visual acuity is correlated with functional visual acuity at higher speeds - Iehisa, Ikko (BMJ Open Ophthalmol, 2019)
OBJECTIVE: To measure the kinetic visual acuity (KVA) which is the ability to identify approaching objects and the functional visual acuity (FVA) which is continuous VA during 1 min under binocular and monocular condition (non-dominant eye shielding) for healthy subjects, and related ocular parameters to explore their correlation and implication in aspect of integrated visual function. METHODS: The mean age of the 28 participants was 38.6±8.9 years (range, 23–57 years; 6 women). A KVA metre (AS-4Fα) and FVA metre (AS-28) were used to measure KVA and FVA, respectively. Multiple regression analysis was conducted to explore correlations among the measured visual function and related parameters, including age, binocularity, best-corrected visual acuity, refraction and tear break-up time. RESULTS: The results of binocular KVA were better than monocular KVA at all speeds. A strong correlation was found between monocular and binocular KVA. The results of binocular FVA were better than monocular FVA (p<0.001) and there was a correlation between monocular and binocular FVA (R=0.638, p<0.001), as well as the maintenance rate for FVA (R=0.228, p=0.003). A linear mixed-effects model revealed that binocularity for KVA prediction was significant at all speeds and FVA was also significant at 60 km/h (p<0.05). CONCLUSION: The current results suggest that both binocularity and FVA may contribute to KVA. TRIAL REGISTRATION NUMBER: UMIN00032385